ӘЖИНИЯЗ ШЫҒАРМАЛАРЫ ТИЛИНДЕГИ ҮРП-ӘДЕТ ҲӘМ ДӘСТҮРЛЕРГЕ БАЙЛАНЫСЛЫ СӨЗЛЕР - Қарлыбаева, Г. (FAN va JAMIYAT, 2020)
The article deals with the phonetic and lexical features of the words belonging to ethnographic layer of the vocabulary. Analyzing the words that were used in those days when the poet created, we see that some of them still exist in the language of local residents and again we are sure that people never lose their national values.